Effect of a Newly-Developed Nutrient Solution and Electrical Conductivity on Growth and Bioactive Compounds in Perilla frutescens var. crispa - Thi Kim Loan Nguyen; Moon-Sun Yeom; Myung-Min Oh (Agronomy, 2021)
We evaluated the effect of a newly-developed nutrient solution of red perilla (NSP) with various electrical conductivity (EC) levels on plant growth, mineral content, and bioactive compounds. Four-week-old seedlings were grown in greenhouse nutrient solution as control (CT) (EC 1–3 dS m−1) or NSP (EC 1–6 dS m−1). NSP 1 dS m−1 induced better growth characteristics, whereas higher EC levels inhibited plant growth. Most of the macro-elements contents significantly decreased under NSP 6 dS m−1, whereas the micro-elements contents fluctuated according to EC levels. Total phenolic concentration in NSP was lower than that in CT, and total phenolic content was highest under NSP 1 dS m−1. Total anthocyanin and antioxidant concentrations and contents increased at lower EC levels. Rosmarinic and caffeic acids concentrations increased at higher EC levels, whereas there were no significant differences in these compound contents among the EC levels. No difference in perillaldehyde concentration was observed, whereas the content was higher at lower EC levels. Overall, these results suggest that NSP 1 dS m−1 is suitable for cultivating red perilla in plant factories.